Dancing as non-pharmacological treatment for healthy agingin the COVID-19 era; a gerontological perspective - Rąglewska, Patrycja; Demarin, Vida (Akademia Wychowania Fizycznego w Poznaniu)
Findings reveal a strong correlation between physical activity and cardiorespiratory fitness, the nervous system, psycho-motor skills, vascular aging, mood, cognition, and the overall quality of life as a result of a regular non-pharmacological treatment. Among many types and modes of physical activities dancing seems superior thanks to the widest spectrum of its impact on the body, including not only physical (fitness endurance, muscle strengthening, flexibility), but also psychological (cognition) and even social needs (satisfying the need of closeness, reducing the sense of loneliness). In view of the above, we summarize current knowledge on the connection between healthy ageing and dancing, which should be especially recommended for older people (>60 y).
Keywords: COVID-19; dancing; physical activity; gerontology